Word illumination - Roslan, Samsilah; Ghiami, Zeinab; Ahmad, Noorlila; Dangku, Jinimy (Universiti Putra Malaysia Press, 2016)
Some people experience a continuous battle in their brain when they attempt to read. This condition akin to an alphabet war is normally referred to as “Dyslexia”. It is neurological in origin and primarily affects the ability to spell, read and write. Literally, it means difficulty with words. Dyslexia sufferers also known as Dyslexics are highly gifted and talented individuals. They learn like other students but with more focus on letter and word recognition. In the education discipline, dyslexic students are addressed as students with special educational needs.